The successful combination of grapefruit juice and venetoclax in an unfit acute myeloid leukemia patient with adverse risk: A case report - Long, Zhangbiao; Ruan, Min; Wu, Wei; Zeng, Qingshu; Li, Qingsheng; Huang, Zhengqi (Frontiers in Oncology, 2022)
Venetoclax combined with hypomethylating agents such as azacitidine and decitabine is the standard regime for the elderly patient with acute myeloid leukemia (AML) unfit for intensive induction therapy. However, many patients struggle with finances and forgo treatments due to the high costs of venetoclax. In this study, we performed the regime with azacitidine, low-dose venetoclax, and grapefruit juice on an unfit AML patient with TP53 mutation. The peak venetoclax concentration (Cmax) and side effects on the patient were also monitored. The patient achieved complete remission with the venetoclax Cmax within the effective concentration range (1,000–3,000 ng/ml) and maintained durable remission until recently. Febrile neutropenia, thrombocytopenia, and pneumonia appeared during the first cycle and were recovered by stimulating agents and antibiotic treatment. This improvement combination approach by drug-food interaction may enlighten other similarly patients with AML, especially those in low-middle income countries.